MENGOPTIMALKAN PEMANFAATAN SUMBER DAYA KENTANG: KETERLIBATAN MASYARAKAT DAN PENINGKATAN KETERAMPILAN DALAM MENGGALI POTENSI TINGGI TEPUNG KENTANG DI DESA WISATA SEMBALUN BUMBUNG - Dharmayani, Ni Komang Tri; Yuanita, Emmy; Ulfa, Maria; Ningsih, Baiq Nila Sari; Sudirman, Sudirman; Septiyana, Maulida; Wardhana, I Gede Adhitya Wisnu (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2024)
Potatoes are one of the staple crops widely cultivated worldwide, with significant production, especially in Europe and North America. However, the economic potential of potatoes has not been fully harnessed, particularly in villages like Sembalun Bumbung, West Nusa Tenggara Province, Indonesia. This article outlines a community engagement approach aimed at enhancing the understanding and skills of the community in utilizing potato flour as a valuable local resource. The implementation methodology involves three main approaches: knowledge transfer, technology transfer, and mentoring. The activities encompass education, hands-on training, as well as testing and evaluating processed potato flour products, particularly noodles. The results of the program demonstrate high enthusiasm among participants, who have successfully produced high-quality potato flour and noodles. This program provides new opportunities for the community to utilize potatoes as an additional source of income and has the potential to significantly boost the village's economy.